The Auditory Marks of the Holocaust within the Complexity of the Radioplay of the GDR (KULT_online, 2012)
This dissertation investigates the auditive code of seven radioplays that originated in the former GDR/Soviet zone of occupation between 1945 and 1989 in their function of generating a social, collective process of recalling the Holocaust. Thereby the radioplay is considered as an independent artwork and within her combination of methods of cultural, medial, and literary studies, the author Manuela Gerlof succeeds in elevating the radioplay to the state of a medium of collective memory. Concurrently she embeds her object of investigation widely in cultural-political and medial-historical contexts, which reveals more kinds of stylistic devices, rather than only one auditory mark.